Behaviors of ALSEP Organic Extractants: an Atomic Perspective Derived from Molecular Dynamics Simulation. Issue 1 (2nd January 2022) - Ta, An T.; Golzwarden, Julian V. A.; Jensen, Mark P.; Vyas, Shubham
ABSTRACT: Molecular dynamics simulations were performed on mixtures of N, N, N′, N′ -tetra(2-ethylhexyl)diglycolamide (T2EHDGA) and 2-ethylhexylphosphonic acid mono(2-ethylhexyl) ester (HEHEHP) extractants in a dodecane-water system in order to understand the organization and interfacial behavior of extractants in the Actinide-Lanthanide Separation (ALSEP) process. The dynamic behavior and coordination environments of these extractants near the interface were investigated as a function of aqueous nitric acid concentration in the range 0–6 M HNO3 . To gain a complete molecular picture of the extractants' interfacial behaviors, the effects of varying acidity were scrutinized in the context of spatial distributions of extractants within a given phase, chemical interactions, interfacial orientation, and extractant conformation. While the composition of the interfacial solvent mixing region changed with increasing acidity, the behavior of both extractants exhibited very little response to the varying acid levels, but in their own distinct manner. HEHEHP was found to express a specific interfacial behavior marked by a stronger affinity for the interface, with the polar POOH head group being oriented toward the interface and the alkyl chains residing in a constrained conformation. The larger and more flexible extractant, T2EHDGA, is less strongly associated with the interfacial region, on average dwells deeper into the organic phase, and displays orientations and conformations that are more like those of bulk organic phase T2EHDGA molecules than the ordered HEHEHP molecules.